Etyka biznesu wobec rozwoju nowoczesnych technologii - Banach, Wiesław (Humaniora. Czasopismo Internetowe, 2025)
The aim of this article is to attempt to answer a very current issue concerning contemporary challenges of business ethics in the face of the development of modern technologies. In particular, the dynamic development of artificial intelligence is unprecedented in history and therefore requires special reflection in the field of sociology, cultural studies, philosophy and ethics. On the one hand, the positives resulting from the effective use of AI in subsequent areas of life are obvious – on the other hand, the signs of a lack of reflection on the civilizational effects of the ubiquitous technological expansion based on artificial intelligence may be disturbing. This deficit is the result of the characteristic of engineers and uncritical supporters of modern technologies: technoenthusiasm, “tunnel thinking” and focusing on a specialized field of knowledge. This causes them to perceive everything separately and thus ignore signals about emerging threats. The challenge for business ethics may be not only to indicate potential dangers, but also to develop appropriate ethical standards, good practices and procedures that will define the principles of our functioning in a reality dominated by modern technologies.